Atrial Fibrillation in Congenital Heart Disease - Irene Martín de Miguel; Pablo Ávila (European Cardiology Review)
The increasing prevalence of AF in a growing population of adults with congenital heart disease (CHD) poses new challenges to clinicians involved in the management of these patients. Distinctive underlying anatomies, unique physiological aspects, a high diversity of corrective surgeries and associated comorbidities can complicate clinical decision-making. In this review, the authors provide an overview of the current knowledge on epidemiology and pathophysiology, with a special focus on the differences to the non-CHD population and the clinical impact of AF in adults with CHD. Acute and long-term management strategies are summarised, including the use of antiarrhythmic drugs, catheter or surgical ablation and prophylaxis of thromboembolism. Finally, gaps of knowledge and potential areas of future research are highlighted.